INOVASI PEMANFAATAN WORD-WALL SEBAGAI MEDIA GAME-BASED LEARNING UNTUK BAHASA ARAB - Jamaluddin Shiddiq (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2021)
Abstract: The Covid-19 pandemic has affected various aspects of the world, including education. The adaptive policy to this phenomenon is distance learning where the use of technology is something that is inevitable. In this case, the use of technology-based media is absolutely necessary so that distance learning is more qualified and effective. This study aims to describe the innovation of making and using the Wordwall application as a game-based media for learning Arabic and is equipped with a description of the situation of learning Arabic during the Covid-19 pandemic. Optimizing the use of the Wordwall application will very likely prepare a person to be able to develop the 4 Arabic skills effectively. The results shows that the steps to use the Wordwall application are: 1) the first step we have to do is create or register an account at https://wordwall.net then complete the data listed in it, 2) Choose create activity then choose one one existing template, 3) Write the title and description of the game, 4) Write the desired content according to the desired type of game, 5) Select done, as the final step when we have finished making it. The following is an example of the use of wordwall media in Arabic learning, which is used during online learning that is After the teacher greets and starts learning in the WA group, then the teacher conveys the objectives and directs the learning to be carried out. After that the teacher asks students to open the link that has been made, by writing the name then start.Keyword: Learning Media, Wordwall, Game-Based Learning